CURRENT ISSUES IN ACCOUNTING FOR FINANCIAL INVESTMENTS - R.A. Botirova; I.Q. Sirojiddinov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Financial investments are financial investments of an economic entity for the purpose of participating in the capital of other enterprises or the purchase of securities issued by various issuers for the purpose of obtaining income from them.